'Getting there': the impact of structured insulin management education in a high ethnic mix population with type 1 and type 2 diabetes. (March 2014) - Fairfield, Jane; Amin, Sayjal; James, June
Abstract: Structured education programmes support and enable people with diabetes to develop self‐management skills. Insulin management central to DAFNE is restricted to those with type 1 diabetes of at least six months' duration and on multiple dose regimens. DESMOND is available for all with type 2 diabetes but does not include guidance on how to self‐manage diabetes with insulin. Our aims were to develop an education programme for people with type 1 or 2 diabetes already on insulin and who may be using a variety of insulin regimens, to enable effective self‐management, improve confidence, reduce hypoglycaemia and enable peer group support. An evidence‐based curriculum, developed in line with NICE principles, was piloted. This consisted of three half‐day sessions held during a one‐month period with up to 10 participants and supporters invited to attend. Four further programmes were held; education was tailored to the individual needs of groups and verbal evaluation was undertaken. Anonymised patient satisfaction questionnaires were posted at programme completion. Audit included clinical data, demographics, patient satisfaction and health care professional assessment of content. There were 40 participants over five courses; 20% (n=8) were type 1, 68% (n=27) were male, average age was 58 years (range 35–82 years), and 55% were South Asian (n=22). In 38 of 40 participants where a recorded pre‐ and three months post‐intervention was available, an average HbA1c reduction of 1.18% was achieved – i.e. 9.02% reduced to 7.84% (75.1mmol/mol reduced to 62.2mmol/mol). Twenty‐five participants (62.5%) returned the survey form: 96% (24/25) said diabetes control improved, and all felt more confident to adjust insulin; 96% (23/24) felt more confident to treat 'hypos' (one stated 'hypos' had not reduced) and 96% (24/25) felt they learned more by attending the programme. This programme met participants' individual needs, increased confidence in insulin management and improved glycaemic control in a high ethnic mix poulation. Copyright © 2014 John Wiley & Sons. Practical Diabetes 2014; 31(2): 54–57